Neutrophil extracellular trap regulators in sickle cell disease: Modulation of gene expression of PADI4, neutrophil elastase, and myeloperoxidase during vaso‐occlusive crisis - Hounkpe, Bidossessi Wilfried; Chenou, Francine; Domingos, Igor de Farias; Cardoso, Evilazio Cunha; Costa Sobreira, Marcondes José de Vasconcelos; Araujo, Aderson S.; Lucena‐Araújo, Antonio Roberto; da Silva Neto, Pedro Vieira; Malheiro, Adriana; Fraiji, Nelson Abrahim; Costa, Fernando Ferreira; Bezerra, Marcos André C.; et al. (Research and practice in thrombosis and haemostasis, 2021)
Recent evidence suggests that generation of neutrophil extracellular traps (NETosis), one of the components of immunothrombosis, is associated with the pathogenesis of both venous thromboembolism and sickle cell disease (SCD). NETosis is a complex process regulated by several proteins such as peptidyl arginine deaminase 4 (PADI4), neutrophil elastase (ELANE), and myeloperoxidase (MPO). Among these regulators, PADI4 is responsible of histone citrullination, an essential step for NETosis. Accordingly, its inhibition has been recently cited as a promising therapeutic strategy for diseases such as SCD. Although attractive, this strategy requires supportive evidence of its role in the pathogenesis of SCD. Patients from two independent cohorts were enrolled in this study. Samples were obtained at steady state (53 patients) or during acute episodes of vaso‐occlusive crisis (VOC; 28 patients) in patients from cohort 1. mRNA was extracted from granulocytes to analyze PADI4, ELANE, and MPO expression by qPCR. Furthermore, plasma activity of PADI4 was assessed from an independent cohort in 15 patients, within 24 hours from admission for VOC. Race‐matched healthy individuals from the same geographic regions were used as controls for each cohort. Higher levels of gene expression of PADI4 and ELANE were observed during VOC. Furthermore, plasma activity of PADI4 was higher in acute VOC when compared to healthy individuals. These results demonstrate that NETosis regulators are modulated during acute VOC, and pave the way for studies of PADI4 inhibition as a therapeutic strategy for acute VOC in SCD.